(untitled) (Research, Society and Development, 2021)
The establishment of adequate standards and principles for the application of norms for the protection of intellectual property rights over cultivars is a fundamental measure for any country, essentially Brazil, one of the richest countries in biodiversity in the world. Thus, the objective of this work was to carry out a systematic review to analyze the scientific production of protection of the main cultivars, to identify existing parameters and methods for the definition of royalty rates and the collection mechanisms adopted. A systematic review was carried out based on articles published in the period of 10 years, from 2009 to 2019, in the scientific bases Scopus and Web of Science. The Boolean terms and operators: “(royalty) and (plant variety or cultivars)” were explored in the title or summary of scientific articles. 83 documents indexed in the Scopus (37) and Web of Science (46) databases were searched. After processing the data and removing duplicate documents, 43 scientific articles remained. With an average publication of 6.7 publications per year. Average of 10 citations per document. A total of 171 authors and 271 co-authors, with five documents having single authorship and an average of 3.1 authors per article. Thus, a study sample of 17 articles was obtained. the journals analyzed did not provide information on how royalties are taxed, they only reported the type of protection and the cultivars studied.